2022
DOI: 10.1038/s41598-022-10246-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transcriptome diversity and in vitro behavior of primary human high-risk breast cells

Abstract: Biology and transcriptomes of non-cancerous human mammary epithelial cells at risk for breast cancer development were explored following primary isolation utilizing conditional reprogramming cell technology from mastectomy tissue ipsilateral to invasive breast cancer. Cultures demonstrated consistent categorizable behaviors. Relative viability and mammosphere formation differed between samples but were stable across three different mammary-specific media. E2F cell cycle target genes expression levels were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Conditional reprogramming is the epitome of personalized medicine; the cells can be directly obtained from a patient, cultured, and used for potential therapeutic approaches [ 23 ]. They can be also used as models for certain cancer types, including rare diseases, e.g., neuroendocrine cervical carcinoma [ 24 , 27 , 132 ], as well as biobanked for future basic and preclinical applications, for example genetic and chemosensitivity testing [ 133 , 134 , 135 , 136 ]. Conditional reprogramming is an inexpensive, easy to use, and robust method [ 25 ].…”
Section: In Vitro Models Of Neuroblastomamentioning
confidence: 99%
“…Conditional reprogramming is the epitome of personalized medicine; the cells can be directly obtained from a patient, cultured, and used for potential therapeutic approaches [ 23 ]. They can be also used as models for certain cancer types, including rare diseases, e.g., neuroendocrine cervical carcinoma [ 24 , 27 , 132 ], as well as biobanked for future basic and preclinical applications, for example genetic and chemosensitivity testing [ 133 , 134 , 135 , 136 ]. Conditional reprogramming is an inexpensive, easy to use, and robust method [ 25 ].…”
Section: In Vitro Models Of Neuroblastomamentioning
confidence: 99%
“…It is interesting to note that the phenotype is completely reversible if these factors are eliminated [66]. Therefore, CR technology can be an ideal model for performing gene profiling analysis [65,67] and drug sensitivity testing for use in breast and other cancer research [68], regenerative medicine, and xenograft studies. An important feature is that these cultures can be used for establishing xenografts [69], patient-derived xenograft cell lines [70], cell cultures from PDXs, and organoid cultures.…”
Section: Conditionally Reprogrammed Cellsmentioning
confidence: 99%
“…One of the limitations is that these cells have a short lifespan when cultured under conventional tissue culture conditions [95]. CR system demonstrated that feeder cell-conditioned medium, together with a Rho-associated kinase (ROCK) inhibitor, can induce inexhaustible and rapid in vitro proliferation of primary epithelial cells from normal and malignant breast tissues [63,65,67,69,80,96].…”
Section: Applications Of Cr In Primary Mammary Epithelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations